Monocytes in inflammatory bowel disease: monocyte and serum lysosomal enzyme activity. - Mee, A; Jewell, D (1980)
1. The activity of a specific lysosomal marker enzyme N'-acetyl-beta-D-glucosaminidase has been determined fluorimetrically in the monocytes and in the serum of patients with Crohn's disease and ulcerative colitis and compared with results obtained from healthy and disease control subjects. 2. Enzyme activities were measured in a monocyte-enriched suspension from a Ficoll-Triosil gradient and in an adherent monocyte preparation. 3. The results indicate that enzyme activity is greater in both monocytes and sera of patients with Crohn's disease and ulcerative colitis than in those from control subjects (P less than 0.01). 4. Enzyme activity within monocytes correlated with disease activity (P less than 0.05). 5. Lysosomal enzymes may contribute to the pathogenesis of the mucosal inflammation in inflammatory bowel disease.